2020
DOI: 10.3390/su13010006
|View full text |Cite
|
Sign up to set email alerts
|

The Adoption of Green Vehicles in Last Mile Logistics: A Systematic Review

Abstract: Widespread adoption of green vehicles in urban logistics may contribute to the alleviation of problems such as environmental pollution, global warming, and oil dependency. However, the current adoption of green vehicles in the last mile logistics is relatively low despite many actions taken by public authorities to overcome the negative externalities of distributing goods in cities. This paper presents a comprehensive literature review on studies investigating the adoption of green vehicles in urban freight tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 179 publications
0
25
0
3
Order By: Relevance
“…Patella et al (2020) showed that interest in using green vehicles in urban logistics has increased significantly as documented by the growing number of publications on this topic in recent years. In the study, three main categories are identified with respect to the various perspectives of papers dealing with urban logistics: (i) Optimization and Planning (O), (ii) Policy (P), and (iii) Sustainability (S) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Patella et al (2020) showed that interest in using green vehicles in urban logistics has increased significantly as documented by the growing number of publications on this topic in recent years. In the study, three main categories are identified with respect to the various perspectives of papers dealing with urban logistics: (i) Optimization and Planning (O), (ii) Policy (P), and (iii) Sustainability (S) [17].…”
Section: Introductionmentioning
confidence: 99%
“…In order to provide an example to illustrate the proposed approach, let us consider a distribution network (from Figure 1a) covering an area of 100 km 2 An example illustrating the course of the UAVs fleet mission, 1 S, and the values of the resistance functions, 2. It is worth noting that the UAVs' routing for mission 1 S is weatherproof for a given weather forecast (i.e., Y k,l (θ) ≥ F (θ)) :…”
Section: Approach To Uav Fleet Online Routingmentioning
confidence: 99%
“…In this paper, we consider the planning of the fleet mission problem for UAVs with highly dynamic and unpredictable environment constraints [1][2][3][4][5]. Typical disruptions in deliveries by UAVs may be caused by ad hoc changes to the deliveries ordered or changing weather conditions, which affect the energy consumption of UAVs and result in their shorter range due to the depletion of batteries [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…• Sustainable LML system design in urban areas: Collaborative urban logistics services should be considered for better consolidation of existing infrastructure and resources to leverage the environmental sustainability of LML deliveries in urban areas. An environmentally-friendly LML system can be operated by fewer delivery vehicles and light-weight vehicles to lessen emissions [104]. Moreover, the innovative digitalization of LML systems is required for the successful development of a sustainable smart city.…”
Section: Innovative Lml Applications Using New Technologies and Syste...mentioning
confidence: 99%